Facial Emotion Recognition and Executive Functions in Insomnia Disorder: An Exploratory Study - Almondes, Katie Moraes de; Júnior, Francisco Wilson Nogueira Holanda; Leonardo, Maria Emanuela Matos; Alves, Nelson Torro (Frontiers in Psychology, 2020)
Background: Clinical and experimental findings have suggested that insomnia is associated with altered emotion processing, such as facial emotion recognition and impairments in executive functions. However, the results still appear non-consensual and have recently been presented by a few number of studies. Accordingly, the aim of the present study was to investigate whether patients with Insomnia disorder will present alterations in recognition of facial emotions and that such alterations will be related to Executive Functions and that Insomnia Disorder patients will exhibit a lower Executive Functions performance when compared to normal controls individuals. Method: A total of 11 individuals (mean age 31.3 ± 9.4) diagnosed with insomnia disorder and 15 control participants (mean age 24.8 ± 4.6) took part in the present cross-sectional study. They completed questionnaires covering socio-demographic data, a sleep and mood evaluation, and a cognitive assessment. Moreover, they underwent a computerized Facial Emotional Recognition test, consisting of facial emotion labeling and facial emotion matching. Results: Individuals with insomnia presented a lower recognition of facial expressions of fear (p = .001; ηp2 = .549; β = .999) and sadness (p = .026; ηp2 = .191; β = .627) in comparison to control volunteers. Perceptual Organization Index (multi-process measure of executive functions) was found to be statistically significant lower in the insomnia group compared to the control group (104.00 vs 115.00, U = 135.5, p = 0.004; Cohen´s d = 1.281). There was a statistically significant association between facial recognition emotional and cognitive processes of in executive functions performance, especially in processes related to the inhibitory control, planning capacity, problem solving and cognitive flexibility in insomnia group. Conclusions: Insomnia disorder impairs the facial emotion recognition of the fear and sadness. Insomniacs with impairment in the facial emotion recognition had impaired performance of executive functions. There is a negative impact on processes related to cognitive-emotional capacity than on processes related to social-emotional recognition. Keywords: insomnia, facial emotional recognition, sleep deprivation, cognition, executive functions